Genome-wide association study identifies variants of GhSAD1 conferring cold tolerance in cotton. (17th December 2021) - Ge, Changwei; Wang, Li; Yang, Yongfei; Liu, Ruihua; Liu, Shaodong; Chen, Jing; Shen, Qian; Ma, Huijuan; Li, Yang; Zhang, Siping; Pang, Chaoyou
Abstract : GhSAD1 regulates cold stress responses in cotton through modulation of C-repeat binding factor activity, and regulation of COLD - REGULATED genes and ABA signalling. Abstract: Cold stress is a major environmental factor affecting plant growth and development. Although some plants have developed resistance to cold stress, the molecular mechanisms underlying this process are poorly understood. Using genome-wide association mapping with 200 cotton accessions collected from different regions, we identified variations in the short chain alcohol dehydrogenase gene, GhSAD1, that responds to cold stress. Virus-induced gene silencing and overexpression in Arabidopsis revealed that GhSAD1 fulfils important roles in cold stress responses. Ectopic expression of a haploid genotype of GhSAD1 ( GhSAD1 HapB ) in Arabidopsis increased cold tolerance. Silencing of GhSAD1 HapB resulted in a decrease in abscisic acid (ABA) content. Conversely, overexpression of GhSAD1 HapB increased ABA content. GhSAD1 HapB regulates cold stress responses in cotton through modulation of C-repeat binding factor activity, which regulates ABA signalling. GhSAD1 HapB induces the expression of COLD - REGULATED ( COR ) genes and increases the amount of metabolites associated with cold stress tolerance. Overexpression of GhSAD1 HapB partially complements the phenotype of the Arabidopsis ABA2 mutant, aba2-1 . Collectively, these findings increase our understanding of the mechanisms underlying GhSAD1 -mediated cold stress responses in cotton.